Vitality: Carnal, Seraphic Bodies - Brian Treanor (Journal of French and Francophone Philosophy, 2017)
This paper reflects on experiences of what i call vitality. Such experiences are neither idiosyncratic (they overlap major themes in Chinese philosophy, among other disciplines) nor mere romanticism (contemporary psychology lends credence to these accounts). Moreover, while some figures in continental philosophy do address the body—as perceiving, as sexed, as political—there has been almost no attention given to the active body of vitality. Drawing from the work of Michel Serres, this paper will uncover some of the significant features of such bodily experiences.